EDUKASI PENGELOLAAN KEUANGAN PADA SISWA SDN 038/XI KOTA SUNGAI PENUH - Syukrawati, Syukrawati; Sarmigi, Elex; Tiara, Tiara; Zapendri, Iqbal; Lestari, Winda (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
It is imperative to provide early financial management education, particularly for a generation that has grown up with access to resources that have made them susceptible to consumerism. This service activity aims to educate students of SDN 038/XI Sungai Full City about the importance of knowledge of managing finances from an early age. The participants in this activity consisted of 46 students, divided into classes III and IV. Activities consist of two stages, namely preparation and implementation. The results of the activity show that students' knowledge is still very limited in relation to financial management. Students are very enthusiastic about participating in activities; this is evident from their activeness in discussion and question-and-answer sessions.